KEMAMPUAN GURU MENGGUNAKAN TEKNOLOGI INFORMASI DAN KOMUNIKASI SELAMA PEMBELAJARAN DARING DI TK NEGERI PEMBINA SABAK AUH - Puspitasari, Enda; Sari, Nofita; Dari, Sri Wulan; Mayasari, Silvi (STKIP Pesisir Selatan, 2021)
This study aims to describe the ability of teachers to use information and communication technology during online learning at the state Kindergarten of the Sabak Auh coach. This type of research is descriptive qualitative, the data source used is primary data, namely directly and data collection techniques using observation and documentation. The location of the research was carried out at the State Kindergarten of the builder of Sabak Auh in mid-July to mid-August. The results of the study indicate the ability of teachers to use information and communication technology (ICT) during the online learning process, namely making videos, communicating via cellphone, creating folders, making assessments, transferring documents, and others. However, in the online learning process, there are also obstacles that occur, namely the difficulty of conditioning students when providing activities through videos, students do not yet have mature readiness in online learning, and difficulties for parents when communicating with teachers via cellphones during learning. online.